Education for zero waste and circular economy sector in Europe - Glavic, Peter (2020)
ABSTRACT: The Erasmus+ project Education for Zero Waste and Circular Economy started in 2018 to fill a gap in Vocational Education and Training, create a new training course and develop interdisciplinary skills needed for new jobs. The consortium of ten partners from nine European countries intends to produce an interactive platform, comprising a Knowledge Hub, an Online Course and a Diagnosis Tool. One of the first activities of the consortium was to analyse the stateof-the-art in zero waste and circular economy in partner countries. The employment situation was considered, along with experience, qualifications and skills needed for trainees. An overview of the existing training was carried out, including educational methods, types of training organizations, duration of activities, and teachers’ and trainers’ qualifications. Basic information on the existing curricula and certification processes was reviewed. A special section was devoted to good practices. Links and references have been collected for each partner state.